2021
DOI: 10.3390/ijms22041963
|View full text |Cite
|
Sign up to set email alerts
|

Adjunctive Nutraceutical Therapies for COVID-19

Abstract: The novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2/COVID-19), is a worldwide pandemic, as declared by the World Health Organization (WHO). It is a respiratory virus that infects people of all ages. Although it may present with mild to no symptoms in most patients, those who are older, immunocompromised, or with multiple comorbidities may present with severe and life-threatening infections. Throughout history, nutraceuticals, such as a variety of phytochemicals from medicinal pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 113 publications
(133 reference statements)
0
32
0
Order By: Relevance
“…In a randomized trial, it was observed that humoral immunity was improved by the supplementation of vitamins A and D among pediatric patients who received influenza vaccination [5]. However, there is still insufficient evidence to provide exact recommendations on vitamin C, D, and E supplementation for the prevention and treatment of COVID-19 [6]. The positive influence of vitamin B 6 on immunity involves activation of innate or adaptive immunity and the influence on the proliferation of immune cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a randomized trial, it was observed that humoral immunity was improved by the supplementation of vitamins A and D among pediatric patients who received influenza vaccination [5]. However, there is still insufficient evidence to provide exact recommendations on vitamin C, D, and E supplementation for the prevention and treatment of COVID-19 [6]. The positive influence of vitamin B 6 on immunity involves activation of innate or adaptive immunity and the influence on the proliferation of immune cells [7].…”
Section: Introductionmentioning
confidence: 99%
“…All three micronutrients are implicated in acute inflammation and in the concept of healthsupporting nutrition to counteract ongoing inflammaging, i.e., the natural progressive age-dependent subclinical inflammatory processes finally causing organ dysfunction and degenerative diseases [9]. Accordingly, micronutrients may be of high relevance for reducing SARS-CoV-2 infection risk, supporting the immune system in combating the virus, and avoiding long-term adverse health issues from COVID-19 [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The spread and mutation rate of influenza and Coxsackie virus were highly elevated in Se-deficient animals [19][20][21]. Accordingly, Coxsackie virus infection causing Keshan disease, i.e., a severe congestive cardiomyopathy, develops endemically in Se-deficient populations [10]. The biologically meaningful threshold currently used to define Se deficiency and sufficiency, respectively, has been based on the occurrence and prevention of this endemic infectious disease [22], or on the full expression of selenoproteins [23].…”
Section: Introductionmentioning
confidence: 99%
“…Given that limited therapeutic modalities are available for the treatment of COVID-19, nutritional modulation of the immune system function has been proposed and is being investigated [ 31 , 32 , 33 , 34 ]. It is widely accepted that normal nutritional status is vital for immune homeostasis [ 35 ], while a number of recently published key studies suggest promising effects of immunonutrition on acute respiratory infections [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%